Extracellular vesicle biomarkers in circulation for colorectal cancer detection: a systematic review and meta-analysis - Xianquan Shi; Xinyu Zhao; Jinru Xue; Erna Jia (BMC Cancer, 2024)
Abstract We provided an overview which evaluated the diagnostic performance of circulation EV biomarkers for CRC from PubMed, Medline, and Web of Science until 21 August 2022.Weidentified 48 studies that involved 7727 participants and evaluated 162 plasma/serum individual EV biomarkers including 117 RNAs and 45 proteins, as well as 45 EV biomarker panels for CRC detection. 12 studies evaluated the diagnostic performance of EV biomarkers for early CRC. The summarized sensitivity, specificity, and AUC value of individual EV RNAs and EV RNA panels were 76%, 75%, 0.87 and 82%, 79% and 0.90, respectively. Meanwhile, those of individual EV proteins and EV protein panels were 85%, 84%, 0.92 and 87%, 83%, 0.92, respectively. These results indicated that EV biomarker panels revealed superior diagnostic performance than the corresponding individual biomarkers. In early CRC, EV biomarkers showed available diagnostic value with the sensitivity, specificity, and AUC value of 80%, 75%, and 0.89.In subgroup analyses, EV miRNAs and LncRNAs held similar diagnostic value with the sensitivity, specificity and AUC value of 75%, 78%, 0.90 and 79%, 72%, 0.83, which was highly consistent with the whole EV RNAs. Significantly, the diagnostic values of EV miRNAs in plasma were marginally higher than those based on serum. In detail, the sensitivity, specificity, and AUC values were 79%, 81%, and 0.92 in plasma, as well as 74%, 77%, and 0.88 in serum, respectively. Therefore, circulation EV biomarkers could be considered as a promising biomarker for the early detection of CRC.